3D network graphene interlayer for excellent interlaminar toughness and strength in fiber reinforced composites. (December 2015) - Jia, Jingjing; Du, Xusheng; Chen, Chao; Sun, Xinying; Mai, Yiu-Wing; Kim, Jang-Kyo
Abstract: A novel CVD grown 3D network graphene is used as interleaves to toughen and strengthen glass fiber reinforced epoxy composite (GF/EP). Remarkable increases of 70% and 206% in mode I and mode II interlaminar fracture energies, respectively, and 36% enhancement in interlaminar shear strength are achieved in GF/EP by incorporating network graphene in the failure-prone mid-plane compared to those composite laminates without interleaves. Pertinent toughening mechanisms include crack deflection and formation of interfacial micro-cracks with significant increase in surface areas owing to the 3D hollow sphere-like graphene wrapping around the epoxy matrix as well as graphene fracture and slippage between adjacent layers.